Dynamic restructuring drives catalytic activity on nanoporous gold–silver alloy catalysts - Zugic, Branko; Wang, Lucun; Heine, Christian; Zakharov, Dmitri N.; Lechner, Barbara A. J.; Stach, Eric A.; Biener, Juergen; Salmeron, Miquel; Madix, Robert J.; Friend, Cynthia M. (Nature materials, 2017)
Bimetallic, nanostructured materials hold promise for improving catalyst activity and selectivity, yet little is known about the dynamic compositional and structural changes that these systems undergo during pretreatment that leads to efficient catalyst function. Here we use ozone-activated silver–gold alloys in the form of nanoporous gold as a case study to demonstrate the dynamic behaviour of bimetallic systems during activation to produce a functioning catalyst. We show that it is these dynamic changes that give rise to the observed catalytic activity. Advanced in situ electron microscopy and X-ray photoelectron spectroscopy are used to demonstrate that major restructuring and compositional changes occur along the path to catalytic function for selective alcohol oxidation. Transient kinetic measurements correlate the restructuring to three types of oxygen on the surface. The direct influence of changes in surface silver concentration and restructuring at the nanoscale on oxidation activity is demonstrated. Our results demonstrate that characterization of these dynamic changes is necessary to unlock the full potential of bimetallic catalytic materials. Dynamic restructuring behaviour and composition changes in bimetallic and nanoporous gold–silver alloys correlate to catalytic activity.